2020
DOI: 10.15316/sjafs.2020.219
|View full text |Cite
|
Sign up to set email alerts
|

Sesamum indicum and Trichilia heudelotii N-hexane and Ethanol Extracts: Ef-fective Remedy Against Callosobruchus maculates F. (Coleoptera: Chrysomeli-dae) Infesting Cowpea Grains

Abstract: Cowpea (Vigna unguiculata L. Walp) is cultivated for its nutritious grains, leaves, and green pods, which plays an important part in the protein requirement for both rural and urban settlers and also a source of quality fodder for livestock and provide cash inflow to the buyers and sellers of the crop (Wakili, 2013; Langyintuo&Lowenberg, 2006). The protein content of cowpea has been classed to be about 23% making it a desirable source of plant based protein (FAO, 2005). It is also rich in starch with seeds co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Nathan et al (2007) reported that, botanicals serve as alternatives to commercially used synthetic insecticides and many of them have often been used against a number of species of stored product insect pests. This finding agrees with that of Ilesanmi et al (2020) who reported high efficacy of sesame leaf ethanolic extracts against C. maculatus. The present study reported highest percentage mortality induced by higher doses of the plants powders.…”
Section: Discussionsupporting
confidence: 93%
“…Nathan et al (2007) reported that, botanicals serve as alternatives to commercially used synthetic insecticides and many of them have often been used against a number of species of stored product insect pests. This finding agrees with that of Ilesanmi et al (2020) who reported high efficacy of sesame leaf ethanolic extracts against C. maculatus. The present study reported highest percentage mortality induced by higher doses of the plants powders.…”
Section: Discussionsupporting
confidence: 93%